ANALISIS KUALITAS PELAYANAN PEREKAMAN KTP-EL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SURABAYA - Citra Ajeng Armanda; Tukiman Tukiman (Jurnal Penelitian Administrasi Publik, 2019)
This research aims to analyze the quality of KTP-el recording services at the Surabaya City Population and Civil Registry Service. The research was conducted at the Surabaya City Population and Civil Registry Service in January 2019. This research is a quantitative descriptive study with a single variable namely service quality. To measure service quality in this study using 9 (nine) service elements listed as SKM elements in PERMENPANRB Number 14 of 2017 concerning Guidelines for Preparing the Public Satisfaction Survey for Public Service Providers. Data analysis techniques used descriptive statistical analysis techniques. This research uses a sampling technique accidental sampling. Data collection techniques were carried out by questionnaire, documentation and literature studies. The results showed that the quality of KTP-el recording services at the Population and Civil Registration Office in Surabaya was "GOOD". This is shown from the results of descriptive analysis of respondents' answer data where the majority of respondents stated that the quality of KTP-el recording services in the Population and Civil Registration Office of Surabaya City is good.Keywords : Public Service, Community Satisfaction, Community Satisfaction Survey